Influence of Methylphenidate on the Frequency of Stuttering: A Randomized Controlled Trial. (October 2015) - Rabaeys, Henk; Bijleveld, Henny-Annie; Devroey, Dirk
Background: Recently, a case report described a decrease in frequency of stuttering after intake of methylphenidate (MPH).Objective: This study was undertaken to investigate if this effect could again be reproduced in a population of young healthy male adult persons with developmental stuttering.Methods: A double-blind randomized crossover trial, with a 2-week washout period, including 15 Dutch-speaking young healthy persons with developmental stuttering, assessed the effects of a single dose of 20 mg MPH compared with placebo on stuttering. Dependent and 1-sample t tests were used to detect significant differences. The end point was the number of stutter moments and self-perceived improvement.Results: MPH yielded a significant decrease in the number of stutter moments when reading and speaking ( P = 0.002), which was not the case with placebo ( P = 0.090). There was a significant improvement from baseline after intake of MPH as compared with placebo ( P = 0.003). Self-perceived improvement with MPH was not significantly better as compared with placebo ( P = 0.28).Conclusions: This study showed that the participants had an objective statistically significant decrease in the frequency of stuttering with MPH, and this was not the case with placebo. This was also the case for a reduction in stutter moments when reading out loud and speaking spontaneously. However, this result was not subjectively perceived by the participants.